Study on Exclusive Breastfeeding practice and related factors among mothers attending in a tertiary care hospital of Bangladesh - Chowdhury, Farzana Rahman; Yasmeen, BH Nazma; Rahman, Shabnam (Northern International Medical College Journal, 2018)
Back ground : Exclusive breastfeeding (EBF) means that the infant receives only breast milk for the first six months of life after birth. In Bangladesh, 55% of children less than 6 months of age are exclusively breastfed according to BDHS 2014. Objectives : To assess the exclusive breast feeding practice and associated factors among children in an urban area ofBangladesh. Method : This cross-sectional study was conducted in Popular Medical College, Dhanmondi, Dhaka, among 80 mothers having infants aged 7-12 months, attending the outpatient department were selected purposively for the study during the period of 1st August 2017 to 31st December 2017. Sample were selected purpasively for the study and predesigned questionnaire were used for data collection. Data analysis was done by using SPSS software version 22. Result : It was found that only 30(37.5%) mother went for regular antenatal checkup and remaining 50 (62.5%) had irregular antenatal check up. But none of them got breastfeeding advice during antenatal visit. Breastfeeding was initiated with in 1 hour of birth in 36(40%) cases and 44 (60%) cases after 1hour of birth. Exclusive breastfeeding (EBF)was found in 40 (50%) children. Among them 30 (75%) were children of housewife mothers. Mixed feeding (breast milk plus formula/ cow’s milk) was given to 30 children among them18 (60%) were the children of housewife mothers.Only formula milk was given to 10 children of them 8(80%) were the children of housewife mothers.Exclusive breast milk was not given by 18(45%) mothers due to job or other occupation whereas 22 (55%) mother did not give EBF due to insufficient breast milk. Conclusion : In the study rate of exclusive breast feeding was 50%. This study also showed that frequency of exclusive breast feeding practice was lower in working mothers than housewife mothers. This study also showed that the speculation of not getting sufficient milk was one of the main reasons for not giving exclusive breastfeeding. Northern International Medical College Journal Vol.10(1) Jul 2018: 343-346